Effect of Isoniazid on the Protoplasmic Viscosity in Mycobacterium tuberculosis - Takayama, Kuni (1975)
The effect of isoniazid on the protoplasmic viscosity in the H37Ra strain of Mycobacterium tuberculosis was determined by using electron spin resonance spectroscopy and a small spin label tempone (2,2,6,6-tetramethylpiperidone-N-oxyl radical). Isoniazid (0.5 μg/ml) caused the internal cellular viscosity to increase gradually over the first 15 h of exposure from a rotational correlation time value (T(c)) of 2.4 × 10(−10) to 3.4 × 10(10) s and then decrease linearly to the control level after 27 h. These results could be interpreted to mean that isoniazid allows a continued and normal synthesis of the protoplasmic components while the rate of increase in the cell volume is reduced. A degradative process may begin after the initial 15-h exposure time, which would cause the reduction in the internal viscosity.